War and Medicine - Radiopoetro Radiopoetro (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1991)
The aim of war is to inflict death in the greatest number and permanent injury among enemy troops, while the aim of medicine is to regain physical and mental health, to maintain medical wellbeing and to prevent diseases and physical disability. Therefore, the aims of war and medicine are in conflict.Paleinology is the science of war and peacewhich studies the causes of war and the conditions for peace and to search for means to realize those conditions, and for the necessary actions to prevent war and to promote peace.At present war is highly mechanized due to the development of technology, and this in turn is brought abou tby the advance of science. The mechanization of war makes possible mass killing, not limited anymore to combatants but includes civilians and children as well, who are ignorant of the purpose of the war. Weapon technology grows rapidly because it is not hampered by economic considerations as is business, but it is forced by political conflictss.Pure science changes human concepts concerning nature, himself and his fate. Applied science has greater influence and attracts wider attention, especially since it is applied to war. Thus, ethics has to follow closely the development of technology.Key Words: war and medicine polemology - human aggression - recombinant DNA - medical ethics